Reforma legal al proceso de sustanciación de los sumarios administrativo instruidos a los Servidores Públicos en el Ecuador - Llanga Vargas, María Sabina (2016)
The development of this research before obtaining a law degree revolves around the problems associated with the right to due process in administrative proceedings initiated against public servants in Ecuador. The present research work to conduct a thorough legal analysis, critical and doctrinal standards on protecting constitutional and civil servants subject to administrative proceedings in state institutions. Through the development of the theoretical and empirical inference has been made that the inquisitorial administrative currently does not comply with the guarantees of due process and the principles pro-trabajador and pro-omine established in our constitutional law. Public servants indicted face procedure lacks fairness, where there are cashed due process, implying that the public servant who has been notified of the initiation of administrative proceedings lack the opportunity to challenge the fact attributed to it effectively. While the administrative proceedings is the way to self-regulation of behavior of people who give their human contingent in state agencies, who in their capacity as public servants in accordance with the public law for the regulation of recruitment, punishment and the worst case, his dismissal, however, the conduct of the administrative investigation procedure in Ecuador suffers from shortcomings and inadequacies that violate legal principles and guarantees, as the effective, impartial and expeditious rights and interests of the public servant . Furthermore, the development of research explores what prescribed laws of other countries, because of its proximity, are influential to our own rules, and which will take some circumstances that can be considered successful in formulating the reform bill. Finally, this work is confirmed by performing a field study regarding the problem to be investigated, for which the criterion has collected a set of legal science professionals by the technique of the survey and the interview, who have expressed their views and opinions regarding the proposed theme, suggesting legal reforms incorporate the procedure of administrative proceedings to ensure a fair and impartial